Pemanfaatan Informasi Teknologi Dalam Meningkatkan Minat Belajar PAI - Nazila Nasywa Maulida; Nurjannah Eka Fitriani; Khalilurrahman Rafi; Nur My Is Kullah (STIT Syekh Muhammad Nafis Tabalong, 2024)
Islamic Religious Education (PAI) is a branch of education that teaches the wisdom and teachings of Islam while preparing each individual to understand and apply them in everyday life. Meanwhile, technology in education is the application of science to education so that learning objectives can be achieved efficiently and effectively. In this article, we discuss the issue of the use of information technology in increasing interest in learning pie among students at the school level as well as the factors that influence the effectiveness of the use of technology in learning Islamic religion among students from the South Sangatta Elementary School. This article aims to help students carry out learning so that learning activities can be carried out more effectively and interestingly and can also produce material that is easy to understand. This article was prepared using qualitative methods using documentation and interviews which were then analyzed to obtain reliable data. The results of this research provide positive input regarding performance in developing students in the appropriate use of technology.